PENDAPATAN USAHATANI KELAPA SAWIT POLA KEMITRAAN DI DESA LAMIN TELIHAN KECAMATAN KENOHAN KABUPATEN KUTAI KARTANEGARA (Income of Oil Palm Farming of Partnership Pattern in Lamin Telihan Village Kenohan Subregency Kutai Kartanegara Regency) - AJURA SUKARMAN; SYARIFAH AIDA; DINA LESMANA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2021)
The revenue is something that motivates farmers to do oil palm farming. The purposes of this study were to determine the production costs, revenue, and income of oil palm farming of partnership pattern in Lamin Telihan Village, Kenohan Subregency, Kutai Kartanegara Regency. The study was conducted from December 2018 to February 2019. Data collected in this study were primary  and secondary data. Sampling in this study was taken purposively. The total samples in this study were 30 respondents. The data analyzel method which used were production costs, revenue, income, and the R/C ratio. The results of research showed that the total of production costs incurred by farmers was an average of IDR4,497,500.00 ha-1 year-1. The revenue obtained by farmers was an average of IDR13,919,425.00 ha -1 year-1. The income earned by farmers was an average of IDR9,412,441.67 ha-1 year-1. The value of R/C ratio was 3.11 meant that oil palm farming is profitable to cultivate.